Effect of Dates (Phoenix dactylifera L.) on Liver of Broiler Chicks Infected with Infectious Bursal Disease Virus. Biochemical and Histological Study - Balqees Hassan Ali1, Ziad Khalaf Jalob2, Zaid Yaseen Ibrahim3, Ahmed Sami Jarad4, Mustafa Salah Hasa (Institute of Medico-legal Publications Pvt Ltd, 2020)
A number of (80) birds (Ross 308) at one day old were obtained from a local hatchery in the area. The birds were allotted into four equal groups (no.=20) and were supplied with basal scientific diet. Palm date (PD) was supplied to G3 and the birds were challenged with virulent Infectious Bursal Disease Virus (IBDV). G4 was treated with palm date 3 days prior to challenge age. G2 was challenged without supplementation of PD. G1 was neither given PD nor challenged. Inclusion rate of PD was 10%. The challenged age was at 33 days old. Blood serum was assayed for evaluation of transaminases and lipid profile 10 days post infection period (PIP). The result showed that histopathological investigation is more accurate in determining the health state of the birds and the palm date have to be supplied in more than 10% to give its significant effect.